Host and immunosuppression-related factors influencing fibrosis occurrence post liver transplantation - Iacob, Speranta; Iacob, Razvan; Manea, Ioana; Uta, Mihaela; Chiosa, Andrei; Dumbrava, Mona; Becheanu, Gabriel; Stoica, Luminita; Popa, Codruta; Brasoveanu, Vlad; Hrehoret, Doina; Gheorghe, Cristian; et al. (Frontiers in Pharmacology, 2022)
Post liver transplantation (LT) fibrosis has a negative impact on graft function. Cytokine production in the host immune response after LT may contribute to the variable CYP3A-dependent immunosuppressive drug disposition, with subsequent impact on liver fibrogenesis, together with host-related factors. We aimed to investigate whether the cytochrome P4503A5*3 (CYP3A5*3) or TBX21 genotypes impact post-LT liver fibrogenesis. Furthermore, the impact of immunosuppressants on cellular apoptosis has been evaluated using human hepatocytes harvested from cirrhotic explanted livers. We have enrolled 98 LT recipients that were followed for occurrence of liver fibrosis for at least 12 months. There was a statistically significant higher trough level of TAC in patients with homozygous CC-TBX21 genotype (7.83±2.84ng/mL) vs 5.66±2.16 ng/mL in patients without this genotype (p=0.009). The following variables were identified as risk factors for fibrosis ≥2: donor age (p=0.02), neutrophil to lymphocyte ratio (p=0.04) and TBX21 genotype CC (p=0.009). In the cell culture model cytometry analysis has indicated the lowest apoptotic cells percentage in human cirrhotic hepatocytes cultures treated with mycophenolate mofetil (MMF) (5%) and TAC+MMF (2%) whereas the highest apoptosis percentage was registered for the TAC alone (11%). The gene expression results are concordant to cytometry study results, indicating the lowest apoptotic effect for MMF and MMF+TAC immunosuppressive regimens. The allele 1993C of the SNP rs4794067 may predispose to the development of late significant fibrosis of the liver graft. MMF-based regimens have a favourable anti-apoptotic profile in vitro, supporting its use in case of LT recipients at high risk for liver graft fibrosis.